Identifikasi Drug Related Problems Pada Pasien Congestive Heart Failure di Rumah Sakit “X” Balikpapan: Identification of Drug-Related Problems in Patients with Congestive Heart Failure at “X” Hospital Balikpapan - Esa Wi Fatma; Nur Masyithah Zamruddin; Adam M. Ramadhan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Heart failure is a condition where the heart fails to pump blood to meet the needs of the tissues. CHF patients are generally given at least 4 types of drugs, namely ACEIs, beta blockers, diuretics and digoxin. As a result, if it is not considered properly, it will be detrimental to the patient. This study is a non-experimental observational study with retrospective data collection on medical record data of patients who meet the inclusion criteria with the aim of knowing patient characteristics, knowing the description of drug use and knowing the incidence of DRPs in CHF patients at Hospital